Manajemen Parenting Untuk Meningkatkan Percaya Diri Anak - Bunyamin, Bunyamin; Munfaqiroh, Siti; Sa’adah, Lailatus; Erawati, Sherly Hesti; Arifin, Zainul; Sugiono, Djoko (STIE Malangkucecwara, 2024)
Educating children is not an easy matter. Parents' mistakes in implementing parenting patterns can influence children's behavior in the future. Therefore, it is important for parents to learn correct parenting principles so they can form positive characters in their children. The aim of parenting to build children's character is to; (1) ensuring the health and safety of children, (2) preparing children to live as productive adults, (3) transmitting cultural values. The aim of implementing this community service program is (1) to contribute to the development of the character of disadvantaged children sheltered by Lazis Sabilillah Malang, (2) to provide knowledge to parents as the main factor that builds the family's personality, (3) to increase self-confidence for Orphaned and underprivileged children under the guidance of Lazis Sabilillah. The targets of this activity are parents of orphans and poor people assisted by Lazis Sabilillah Malang. This Community Service Program activity was held on Monday, September 11 2023, located at the Sabilillah Mosque in Malang and went smoothly. Parents of orphans and poor people assisted by Lazis Sabilillah are very happy, they have gained knowledge about how to build children's character so that they have self-confidence and a good and strong personality.